Financial Sustainability Through Effective Risk Management Practices - Vasumathy Hariharan, S. (Indian Journal of Finance, 2014)
The contribution of Indian small and medium export firms to the total gross domestic product and employment generation has been commendable. These firms were in the limelight recently because of their currency risk management practices. A few firms were able to manage risks effectively, whereas many firms suffered losses in spite of taking positions in derivatives. The bankers also allegedly mis-sold derivatives to these firms. Against this background, the present study was conducted with randomly selected 330 firms to examine the currency risk management practices of select export firms on three dimensions: exposure management, hedging decisions, and derivative decisions. Through this study, an evaluation was made of their knowledge levels, requirements, and usage of suitable hedging tools apart from analyzing their risk management policies and practices. As the firms varied in their practices, a classification of firms using K-means clustering, based on the strategies used by them, was attempted, resulting in three discriminated groups. A prediction of future group associations of firms with the given risk management outlook, using discriminant analysis, yielded results with 98% accuracy. Profiling the export firms based on their risk management practices could be used by financial institutions, legal advisors, auditors, and so forth to render advice effectively regarding financial products.